The distribution of jhp0940, jhp0945, jhp0947, jhp0949 and jhp0951 genes of Helicobacter pylori in China - Gong, Yanan (BMC Gastroenterol, 2015)
BACKGROUND: The plasticity region of Helicobacter pylori (H. pylori) is a large chromosomal segment containing strain-specific genes. The prevalence of the plasticity region genes of the H. pylori strains in China remains unknown. The aim of this study was to examine the status of these genes and to assess the relationship between the genes and the diseases caused by H. pylori infection. METHODS: A total of 141 strains were isolated from patients with chronic active gastritis (CAG), peptic ulcer disease (PUD) and gastric carcinoma (GC). The prevalence of jhp0940, jhp0945, jhp0947, jhp0949 and jhp0951 was determined using PCR, and the results were analyzed using the chi-squared test. RESULTS: The prevalence rates of jhp0940, jhp0945, jhp0947, jhp0949 and jhp0951 in the H. pylori strains were 42.55, 51.06, 20.57, 56.03 and 63.12 %, respectively. The prevalence rates of jhp0940 were similar in the isolates from the CAG, PUD and GC patients, and there was no association between the jhp0940 status and any of the diseases. In contrast, the prevalence rates of jhp0945, jhp0947, jhp0949 and jhp0951 were significantly higher in the PUD and GC isolates than in the CAG isolates (p < 0.01). A univariate analysis showed that jhp0945, jhp0947, jhp0949 and jhp0951 increased the risk of PUD, while only jhp0951 was significantly associated with PUD in the multivariate analysis (p = 0.0149). The jhp0945-positive isolates were significantly associated with an increased risk for GC (p = 0.0097). CONCLUSION: The plasticity region genes are widely distributed in Chinese patients, and a high prevalence of these genes occurs in more serious diseases. Therefore, jhp0951 status is an independent factor associated with the development of PUD, and jhp0945 may predict the future development of GC in patients with CAG and is considered to be the best candidate disease marker for H. pylori-related diseases.